Gastric Bypass Surgery Produces a Durable Reduction in Cardiovascular Disease Risk Factors and Reduces the Long‐Term Risks of Congestive Heart Failure. Issue 5 (23rd May 2017) - Benotti, Peter N.; Wood, G. Craig; Carey, David J.; Mehra, Vishal C.; Mirshahi, Tooraj; Lent, Michelle R.; Petrick, Anthony T.; Still, Christopher; Gerhard, Glenn S.; Hirsch, Annemarie G.
Abstract : Background: Obesity and its association with reduced life expectancy are well established, with cardiovascular disease as one of the major causes of fatality. Metabolic surgery is a powerful intervention for severe obesity, resulting in improvement in comorbid diseases and in cardiovascular risk factors. This study investigates the relationship between metabolic surgery and long‐term cardiovascular events. Methods and Results: A cohort of Roux‐en‐Y gastric bypass surgery (RYGB) patients was tightly matched by age, body mass index, sex, Framingham Risk Score, smoking history, use of antihypertension medication, diabetes mellitus status, and calendar year with a concurrent cohort of nonoperated control patients. The primary study end points of major cardiovascular events (myocardial infarction, stroke, and congestive heart failure) were evaluated using Cox regression. Secondary end points of longitudinal cardiovascular risk factors were evaluated using repeated‐measures regression. The RYGB and matched controls (N=1724 in each cohort) were followed for up to 12 years after surgery (overall median of 6.3 years). Kaplan–Meier analysis revealed a statistically significant reduction in incident major composite cardiovascular events ( P =0.017) and congestive heart failure (0.0077) for the RYGB cohort. Adjusted Cox regression models confirmed the reductions in severe composite cardiovascular events in the RYGB cohort (hazard ratio=0.58, 95% CI=0.42–0.82). Improvements of cardiovascular risk factors (eg, 10‐year cardiovascular risk score, total cholesterol, high‐density lipoprotein, systolic blood pressure, and diabetes mellitus) were observed within the RYGB cohort after surgery. Conclusions: Gastric bypass is associated with a reduced risk of major cardiovascular events and the development of congestive heart failure.